Efecto antibacteriano in vitro del extracto alcohólico de Medicago sativa “Alfalfa” en cultivos de Klebsiella pneumoniae cepa clínica - Luján Aguilar, Silvia Milagros (2020)
Klebsiella pneumoniae is a Gram-negative bacterium, found as saprophyte in humans and other mammals, colonizing a variety of sites in the body. Alfalfa is a forage plant with antibacterial activity. Objective: The purpose of the present research was to evaluate the in vitro antibacterial effect of the alcoholic extract of Medicago sativa "Alfalfa" in cultures of Klebsiella pneumoniae clinical strain. Method: The alfalfa came from the district of Laredo (La Libertad, Peru), by means of the method of maceration with alcohol at 70% alcoholic extract was obtained at concentrations of 250 mg/ml and 500 mg/ml; a phytochemical march was carried out and the antibacterial activity was determined by the modified Kirby Bauer method and Minimum Inhibitory Concentration (MIC). Results: The concentrations 250 mg/ml and 500 mg/ml of alcoholic extract of alfalfa, by means of the modified Kirby Bauer method, showed inhibition of 8.7 mm and 10.4 mm respectively, both being significant; likewise there was a significant effect with the CIM method when compared with the negative control. Conclusion: The alcoholic extract of Medicago sativa tube antibacterial effect on cultures of Klebsiella pneumoniae clinical strain.